Analisis Pemetaan Perseptual Dan Preferensi Kunjungan Wisata Religi Kota Banjarmasin Di Masa Pandemi Covid-19 - Hakim, Ahmad Firman; Taharuddin, Taharuddin (Universitas Lambung Mangkurat, 2023)
Analysis of Perceptual Mapping and References to Religious Tourism Visits in Banjarmasin City during the Covid19 Pandemic (Study on Tourists in Banjarmasin City). Supervised by Taharuddin. This study aims to identify and explain perceptual mapping, visit preferences, predictions of destination religious destinations in Banjarmasin City with perceptual mapping analysis and tourist visit preferences. This research is quantitative research using SPSS for Windows version 26 with Multidimensional scaling analysis method. The sample in this study used the Matchin & Campbell formula with a sample of 150 respondents. The analytical tools used are descriptive analysis, perceptual mapping analysis and thrustone case analysis. Based on the results of the analysis carried out, the results show that the destinations of the Sabilal Muhtadin Grand Mosque, Jami Mosque, and Habib Basirih Tomb which will be crowded Keywords: Perceptual Mapping, Visit Reference, Tourism and Religion